2007
DOI: 10.1097/nen.0b013e31804567d7
|View full text |Cite
|
Sign up to set email alerts
|

IQGAP1 and IGFBP2

Abstract: Clinical treatment decisions and the survival outcomes of patients with gliomas are directly impacted by accurate tumor classification. New and more reliable prognostic markers are needed to better identify the variable duration of survival among histologically defined glioma grades. Microarray expression analysis and immunohistochemistry were used to identify biomarkers associated with gliomas with more aggressive biologic behaviors. The protein expression of IQGAP1 and IGFBP2, when used in conjunction with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…Although an increasing number of studies has aimed to elucidate the expression of IQGAP1 in various types of cancer, including lung cancer (21), endometrial cancer (22), ovarian cancer (23), gastric cancer (24), colon cancer (25), hepatic carcinoma (26), breast cancer (27) and even glioma (28), the molecular roles of IQGAP1 remain to be understood and the correlation between clinical outcomes and IQGAP1 expression in human malignant tumors require further investigation. The present study indicated that IQGAP1-siRNA inhibited the proliferation and metastasis of U251 and U373 glioma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although an increasing number of studies has aimed to elucidate the expression of IQGAP1 in various types of cancer, including lung cancer (21), endometrial cancer (22), ovarian cancer (23), gastric cancer (24), colon cancer (25), hepatic carcinoma (26), breast cancer (27) and even glioma (28), the molecular roles of IQGAP1 remain to be understood and the correlation between clinical outcomes and IQGAP1 expression in human malignant tumors require further investigation. The present study indicated that IQGAP1-siRNA inhibited the proliferation and metastasis of U251 and U373 glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to glioma, patients with glioblastoma and negative IQGAP1 expression have been reported to survive for >3 years (28). Studies regarding the effects of IQGAP1 on cell proliferation are increasing.…”
Section: Discussionmentioning
confidence: 99%
“…IQGAP1 could impair the intrinsic GTPase activity of CDC42, thus stabilizing CDC42 in its activated form [34]. IQGAP1 was detected to be highly expressed in several cancer types, and resulted in poor prognosis and survival of patients [35,36,37]. As an effector of CDC42, IQGAP1 can bind directly to CDC42 and has been implicated in the modulation of cell architecture and regulation of exocytosis in human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IGFBP-2 is significantly associated with the Ki-67 labeling index in gastric carcinoma 55. In addition, over the past 15 years, results of several studies reporting increased expression of IGFBP-2 have correlated it with poor clinical GBM patient outcomes 5659. Moreover, recent studies have reported that plasma IGFBP-2 levels could predict the clinical outcomes of GBM patients 25,60,61.…”
Section: Discussionmentioning
confidence: 99%